(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article analyzes the problem of using coping strategies by students of different sexes. The concepts of coping and coping-strategies are considered. Copying behavior strategies were defined as certain ways of behaving in difficult (or stressful) situations. The diagnostic results of coping strategies in youth are given. The research results of stress reaction methods are presented. The difference between the results of the research between children is demonstrated: students prefer to find the right solutions and try to apply adequate and effective coping strategies. Psychological and pedagogical methods of forming the right coping strategy for overcoming. students’ life difficulties are proposed.